Answer/Step-by-step explanation:
Given:
f(x) = -3x + 4
✔️First row, find x when f(x) = 4:
Substitute f(x) = 4 into the equation
4 = -3x + 4
4 - 4 = -3x
0 = -3x
Divide both sides by -3
0/-3 = x
x = 0
✔️ Second row, find f(x) when x = -1:
Substitute x = -1 into the equation
f(-1) = -3(-1) + 4
f(-1) = 3 + 4
f(-1) = 7
✔️ Third row, find f(x) when x = 1:
Substitute x = 1 into the equation
f(1) = -3(1) + 4
f(1) = -3 + 4
f(1) = 1
✔️ Fourth row, find x when f(x) = 9:
Substitute f(x) = 9 into the equation
9 = -3x + 4
9 - 4 = -3x
5 = -3x
Divide both sides by -3
5/-3 = x
x = -⁵/3